Structural, Electrochemical, Bacterial Activity, Hardness, and Thermal Properties of Mg Alloy with Various Zn Contents - Premono, Agung; Basori, Imam; Sukarno, Ragil; Susetyo, Ferry Budhi; Alhamidi, A. Ali; Anugrah, Hanif Setia; Muqafillah, Mochammad Fajr Dzakwan; Yudanto, Sigit Dwi; Hasbi, Muhammad Yunan; Situmorang, Evi Ulina Margareta; Edbert, Daniel; Mutiara, Etty; Kriswarini, Rosika; Jamaludin, Agus; Ajiriyanto, Maman Kartaman; Rosyidan, Cahaya (Science and Technology Indonesia, 2026)
Magnesium (Mg) alloy is used for various medical purposes, such as bone implants. In the present study, MgAlSixZn alloys were created utilizing the gravity casting by adding various Zinc (Zn) (x is 0, 0.5, 1.2, and 1.7 wt.%) and then homogenized at 400 ◦C for around two hours. MgAlSixZn as homogenized samples were investigated for microstructure, phase structure, electrochemical behavior, surface morphology, bacterial activity, hardness, and thermal behavior using an optical microscope, XRD, Potentiostat, SEM-EDS, digital camera, Vickers hardness test, and Thermogravimetric apparatus, respectively. Several findings include that increasing Zn content implies a grain growth inhibition mechanism facilitated by Zn segregation at grain boundaries, increased corrosion rates, a rise in the hardness, and increased weight loss. It should be noted that the increase in the corrosion rate and weight loss occurs linearly for Zn addition in the Mg alloy until 1.2 wt.%. An increase in Zn concentration causes the peak shift in MgAlSi-based alloy samples, but no crystallographic orientation is apparent. At the end, the highest corrosion rate and inhibition area are observed in MgAlSi1.2Zn, which indicates that it is suitable for biodegradable orthopedic wire.